Twentieth Century Mythologies: Dumaezil, Laevi-Strauss, Eliade - Dubuisson, Daniel (Taylor and Francis, 2014)
Myths have intrigued scholars throughout history. 'Twentieth Century Mythologies' traces the study of myth over the last century, presenting the key theories of mythology and critiquing traditional definitions of myth. The volume presents the work of influential scholars in mythology: the noted Indo-Europeanist Georges Dumezil, the structuralist anthropologist Claude Levi-Strauss, and the historian of religions Mircea Eliade. 'Twentieth Century Mythologies' is an indispensable resource for scholars of religion and myth and for all those interested in the history of ideas